Second order duality for multiobjective programming with cone constraints - Tang, LiPing; Yan, Hong; Yang, XinMin (Science China. Mathematics, 2016)
We focus on second order duality for a class of multiobjective programming problem subject to cone constraints. Four types of second order duality models are formulated. Weak and strong duality theorems are established in terms of the generalized convexity, respectively. Converse duality theorems, essential parts of duality theory, are presented under appropriate assumptions. Moreover, some deficiencies in the work of Ahmad and Agarwal (2010) are discussed.